2022
DOI: 10.1021/acsomega.1c07063
|View full text |Cite
|
Sign up to set email alerts
|

First-Principles Exploration into the Physical and Chemical Properties of Certain Newly Identified SnO2 Polymorphs

Abstract: Tin dioxide (SnO 2 ) is one of the transparent conductive oxides that has aroused the interest of researchers due to its wide range of applications. SnO 2 exists in a variety of polymorphs with different atomic structures and Sn–O connectivity. However, there are no comprehensive studies on the physical and chemical properties of SnO 2 polymorphs. For the first time, we investigated the structural stability and ground-state properties of 20 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 64 publications
(131 reference statements)
2
19
0
Order By: Relevance
“…Compared to the other stable polymorphs, the 2H-MoSe 2 polymorph shows high vibrational energy, and the free energy is high for the 2H-MoSe 2 polymorph. At extremely low temperatures, entropy stays constant for all polymorphs, and at an absolute zero, it becomes zero . At 1000 K, 2T-MoSe 2 , 3H b -MoSe 2 , and 1H-MoSe 2 polymorphs obtained the constant value 170 J K –1 mol –1 , but 1H-MoSe 2 polymorph showed 140 J K –1 mol –1 of energy as a function of temperature.…”
Section: Resultsmentioning
confidence: 91%
See 3 more Smart Citations
“…Compared to the other stable polymorphs, the 2H-MoSe 2 polymorph shows high vibrational energy, and the free energy is high for the 2H-MoSe 2 polymorph. At extremely low temperatures, entropy stays constant for all polymorphs, and at an absolute zero, it becomes zero . At 1000 K, 2T-MoSe 2 , 3H b -MoSe 2 , and 1H-MoSe 2 polymorphs obtained the constant value 170 J K –1 mol –1 , but 1H-MoSe 2 polymorph showed 140 J K –1 mol –1 of energy as a function of temperature.…”
Section: Resultsmentioning
confidence: 91%
“…The physical quantities and orientation of Young’s modulus ( E ) and Poisson’s ratio (ν) can be used to show that polymorphs have isotropic characteristics. Young’s modulus ( E ) determines the polymorph’s orientation, which is derived using the given elastic compliance constants . Young’s modulus ( E ) surface should be perfectly spherical for isotropic materials.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The symmetry of orthorhombic In 2 O 3 polytypes is expressed by the D 2 h ( mmm ) point group and the irreducible representation is Γ = 12 A g + 6 B 1g + 12 B 2g + 6 B 3g + 11 B 1u + 5 B 2u + 11 B 3u ; it consists of four Raman active modes ( A g , B 1g , B 2g , B 3g ) and three IR-active modes ( B 1u , B 2u , B 3u ). 56 Raman spectroscopy of In 2 O 3 - O 1 and In 2 O 3 - O 3 has shown that the frequency spectrum with the strongest peak at 496, and 611 cm –1 , respectively, corresponds to the Raman-active A g mode. The nondegenerate mode A g represents out-of-plane vibrations and they can be symmetric stretch or bend with respect to the principal axis of symmetry of the In 2 O 3 molecule.…”
Section: Resultsmentioning
confidence: 99%